Planificación estratégica de mercado de la empresa creaciones arte hogar de la ciudad de Loja. - Robles Moreno, Yadira Fernanda (2012)
In the administration of the Company Creations Art Home several problems can settle down among which can highlight the lack of incentives for clients, training of the personnel in attention to the client. These aspects are necessary that they are overcome to be able to optimize the profitability of the company. For the development of the present work the methodology was continued that corresponds to a strategic plan, he/she was also defined the internal and external conditions by means of the use of the main FODA, those that it allowed us to know the situation of the company objectively. Inside this work one also carries out an I diagnose situational, through the external analysis and I intern of the company information that served like base to apply those in hills to the internal and external actors of the same one. Then it was made the study and analysis FODA, with their wombs of valuation with the purpose of to quantify and to identify their potentialities like managerial limitations. According to this analysis FODA intended the implementation of 5 strategic objectives to improve the organizational, administrative structure and of administration, which will be described next: To implement affiliation cards and discount for clients that are faithful to the company with their visit. The company creations art home should implement purchase incentives in each one of its sales for this way to have more its clients' welcome The company" Creations art Home" it should implement the training to their personnel about the service that ready to the client. To achieve that the training and consultant ship in the courses of handiworks that it offers the company to their clients are better organized and dictations. To carry out better purchase offers for the potential clients, that is to say for those that carry out their bigger purchases. In definitive the total cost of this Strategic Plan of Market ascends to a value of $ 2820 American dollars. Finally the summations and more convenient recommendations were made for this organization, to be better in the administrative, organizational environment and in question to their services.